Cartography of the Archaeological Study of the Ananyino Culture Sites in the Vyatka River Basin - U. V. Komarova (Историко-географический журнал)
The article provides an overview of significant studies of the Vyatka-Vetluga Ananyino cultural and historical area (AKIO), as well as a description of the chronology of the discovery of these sites in the Vyatka River basin. The author uses the mapping method to visualize the distribution of the AKIO sites. The cartographic method serves as a tool not only for displaying and analyzing data, but also for identifying the relationships between sites, determining their density and the dynamics of discovery over time. The article illustrates the author’s research with three maps, each of which is presented with a specific purpose. The first map shows the routes of the main expeditions from the 18th to the 20th centuries. The second map shows the discovery dates of the sites. The third map visualizes the distribution of the AKIO sites depending on soil conditions. In addition, this study is aimed at systematizing knowledge about AKIO and identifying trends in its study. There are several criteria for structuring the material: the type and name of the site, its dating, the researchers involved in the study, the total area of the monument and the area studied. These data enable accurate tracing the development of archaeological research in the Vyatka River basin from the very first discovery to the present day. The article highlights the importance of the cartographic method in the context of archaeology, demonstrating how data visualization can facilitate the identification of patterns and trends in the distribution of the Ananyino culture sites.